Eksekusi Objek Jaminan Fidusia yang Berada Dibawah Penguasaan Debitur yang Wanprestasi Pasca Putusan MK Nomor 2/PUU XIX/2021 (Studi Putusan Nomor 83/Pdt.G/2022/PN.Pbr) - Satya Gunawan, Grace Wahyu; Zeihan Shona Shafira; Yanti Agustina; Chris Anggi Natalia B (Universitas Medan Area, 2025)
The Constitutional Court Decision No. 2/PUU-XIX/2021 affirms that the execution of fiduciary collateral objects may not be carried out unilaterally by the creditor if the debtor refuses to voluntarily surrender the object. Under such circumstances, execution must be conducted through judicial proceedings to ensure legal protection and uphold the principle of justice for both parties. This study aims to examine the judicial considerations in the Decision of the Pekanbaru District Court No. 83/Pdt.G/2022/PN.Pbr concerning the execution of fiduciary collateral still under the control of a defaulting debtor. The research applies a normative juridical approach and case study method by analyzing the application of legal norms following the Constitutional Court's decision. The findings indicate that the judge considered the principles of fairness, balanced legal protection, and legal certainty in rendering the verdict. The study concludes that, in accordance with constitutional mandates post-Decision No. 2/PUU-XIX/2021, the execution of fiduciary security objects contested by the debtor must obtain judicial authorization.